THE INFLUENCE OF ENVIRONMENTAL POLICY ON DEVELOPMENT IN DEVELOPING COUNTRIES - Pramana, M. Zidan (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2025)
In general, developing countries have more problems with construction than developed countries. Development has serious environmental problems in developing countries. Development that is not environmentally friendly can damage ecosystems and threaten the existence of natural resources. The importance of paying attention to environmental impacts in every development policy. Risk reduction and environmental protection need to be discussed in planning and this research is carried out by reviewing literature articles, journals and other related publications. Literature Review Method Collect and analyze in advance information from researchers, inequality of access to environmental resources. This information is analyzed to determine the effect of environmental policies on development in developing countries, a factor causing development in developing countries. The environment has a very important function for human life. The environment is needed by man for his survival and provides a variety of needs. It is important to develop balanced environmental policies that support economic growth while reducing the impact of development on environment. Environmental policy has a significant influence on development in developing countries, and needs to be considered in developing policies that can better support sustainable development in developing countries that are sustainable and environmentally friendly to protect the quality of the environment.